2008
DOI: 10.1017/s1751731107000936
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lipid accumulation in 3T3-L1 cells: insulin-independent and combined effects of fatty acids and insulin

Abstract: The insulin-independent and combined effects of fatty acids (FA; linoleic and oleic acids) and insulin in modulating lipid accumulation and adipogenesis in 3T3-L1 cells was investigated using a novel protocol avoiding the effects of a complex hormone 'induction' mixture. 3T3-L1 cells were cultured in Dulbecco's modified Eagle's medium (DMEM) plus serum (control) or in DMEM plus either 0.3 mmol/l linoleic or oleic acids with 0.3 mmol/l FA-free bovine serum albumin in the presence or absence of insulin. Cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 45 publications
5
26
0
Order By: Relevance
“…This property of trehalose is considered to result in the suppression of adipocyte hypertrophy. Insulin promotes storage of lipids in adipocytes, and its excessive secretion can cause hypertrophy of these cells (13,14). Thus, the results of this study suggest the possibility that excessive insulin secretion can be reduced by ingesting trehalose with meals.…”
Section: Discussionmentioning
confidence: 68%
“…This property of trehalose is considered to result in the suppression of adipocyte hypertrophy. Insulin promotes storage of lipids in adipocytes, and its excessive secretion can cause hypertrophy of these cells (13,14). Thus, the results of this study suggest the possibility that excessive insulin secretion can be reduced by ingesting trehalose with meals.…”
Section: Discussionmentioning
confidence: 68%
“…Both anti-adipogenic effects of conjugated linoleic acids (reviewed in [31]) and adipogenic effects of other polyunsaturated fatty acids (PUFA) and monounsaturated fatty acids (MUFA) [11,12,35,46] have been reported. Several of these studies have also focused on induction of gene expression of the key transcription factors that regulate adipogenesis, PPARγ and C/EBPα [22,35,61]. Amri et al [3], demonstrated that α-linolenate can induce ap2 (adipocyte fatty acid binding protein or FABP4) gene expression in Ob1771 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Short-chain and medium-chain fatty acids (MCFA) showed weaker induction of ap2 gene expression than longchain fatty acids (LCFA) [3]. Recently, we have shown that OA and LA induced triglyceride accumulation, PPARγ, and GLUT4 (glucose transporter 4) protein expression in 3T3-L1 cells [35]. In addition, MCFA, octanoate (C8:0) and decanoate (C10:0), were shown to induce gene expression of AD specific transcription factors such as, PPARγ, C/ EBPα, SREBP-1c, FABP4, and LPL [22,61].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oil Red O-stained fat droplets are observed in the differentiated ADC. Unsaturated fatty acids as inducers of adipogenic differentiation were demonstrated in various kinds of cells including multipotent muscle stem cells (Wada et al, 2002), immortalized human myogenic progenitors (Hashimoto et al, 2006) and human cancer cells (Ruiz-Vela et al, 2011), as was validated by de novo biogenesis of lipid droplets (Fujimoto et al, 2007) and the adipogenic marker PPAR-gamma expression (Kokta et al, 2008). PPAR-gamma expression in ADC is shown in Fig.…”
Section: Resultsmentioning
confidence: 92%